Maqashid syariah dalam implementasi perekonomian. - may-saroh., may-saroh (Maliki Interdisciplinary Journal, 2024)
From the research conducted, it has a goal, namely to understand the economic processes that have occurred in the midst of society. Is the economy in line with the "maqashid syariah" Islamic provisions or is there a possibility of implementation that is still far from the sharia law? The author uses qualitative analysis methods. Data collection was carried out using secondary data with existing sources. implementation of maqashid syariah needs to be done at this time, because as Muslims, they should carry out Islamic teachings in muamalah. In addition, the results of the research conducted can be used as further research. Meanwhile, in facing the ever-changing economic life, a foundation is needed as a basis for travel and theory is needed as a guide in making decisions.